The protein kinase Ire1 impacts pathogenicity of Candida albicans by regulating homeostatic adaptation to endoplasmic reticulum stress - Sircaik, Shabnam (Cell Microbiol, 2021)
The unfolded protein response (UPR), crucial for the maintenance of endoplasmic reticulum (ER) homeostasis, is tied to the regulation of multiple cellular processes in pathogenic fungi. Here, we show that Candida albicans relies on an ER‐resident protein, inositol‐requiring enzyme 1 (Ire1) for sensing ER stress and activating the UPR. Compromised Ire1 function impacts cellular processes that are dependent on functional secretory homeostasis, as inferred from transcriptional profiling. Concordantly, an Ire1‐mutant strain exhibits pleiotropic roles in ER stress response, antifungal tolerance, cell wall regulation and virulence‐related traits. Hac1 is the downstream target of C. albicans Ire1 as it initiates the unconventional splicing of the 19 bp intron from HAC1 mRNA during tunicamycin‐induced ER stress. Ire1 also activates the UPR in response to perturbations in cell wall integrity and cell membrane homeostasis in a manner that does not necessitate the splicing of HAC1 mRNA. Furthermore, the Ire1‐mutant strain is severely defective in hyphal morphogenesis and biofilm formation as well as in establishing a successful infection in vivo. Together, these findings demonstrate that C. albicans Ire1 functions to regulate traits that are essential for virulence and suggest its importance in responding to multiple stresses, thus integrating various stress signals to maintain ER homeostasis.